Periklanan Dalam Perspektif Etika Islam - Mustafa Mustafa (An-Nida', 2019)
Advertising is the main element of a company's promotion tool. Most companies spend a lot of money on advertising around 25% of the total budget. Advertising is very important to increase an organization's revenue. But recently, some advertisements made false promises to attract new customers to buy products that are strictly prohibited in Islam. In this paper, we try to establish several dimensions of advertising supported by Islam. There should be no practice of fraud, fraud, misrepresentation, coercion, and injustice in measurement; and there shouldn't be anything unfair. In this article the author tries to find out the Islamic point of view of advertising where the public will find advertisements working as they should